Pair-Compton cascading in a spatially varying anisotropic radiation field - Protheroe, R. J.; Mastichiadis, A.; Dermer, C. D. (1992)
When energetic electrons Compton scatter soft photons in the Klein-Nishina regime, the produced gamma rays are subject to photon-photon pair attenuation, and a pair-Compton cascade results. We examine the formation of such cascades in the spatially varying photon fields encountered by high-energy electrons and photons emitted from luminous compact objects. Constraints on the geometry of the soft photon source and the location of the gamma-ray production site are deduced from observations of 100 MeV and TeV gamma rays emitted by galactic compact objects and active galactic nuclei.